### How matrix X1 X2 equals matrix X1 X2?

i think its pretty much the same thing because matrix X1 X2 IS ACTUALLY X1 X2

### How much dirt is in a hole that measure 2'x2'x2'?

I believe that would be 2 feet deep, 2 feet wide, and 2 feet long.

### How much dirt is in a hole 3'x5'x2'?

There would be no dirt in a hole, but the hole would fit 30 cubic feet.

### How much dirt is in a 3'x5'x2' hole?

30 cubic feet of dirt have been removed, and no dirt remains in the hole.

### What are the factors of x2 x 20?

Operational signs would make this so much easier. If that's x2 - x - 20, the answer is (x + 4)(x - 5). If that's x2 + x - 20, the answer is (x + 5)(x - 4).

### What is 3x4 plus 5x3 plus x2 - 5 divided by x 2?

3x4 plus 5x3 plus x2 - 5 divided by x 2 =[(3x4) + (5x3) + (x2 - 5)]/x2 = (12 + 15 + x2 -5)/x2 = (27 - 5 + x2)/x2 = (22 + x2)/x2

### What is the value of X2 plus X?

The answer would be 3x if 'X2' is '2x', but if 'X2' is x2, then the total answer would be x2 + x.

### What is the difference between the xenith x1 and x2?

The Xenith X1 and X2 are very similar. The biggest differences are in the shock bonnet, and the fit system. The X1 incorporates a metal cable in the fit system, where the X2 simply uses a continuation of the chin strap in the fit-seeker. As far as protection goes.....they're virtually the same. You can wear the X2 with as much confidence as the X1.

### X6 plus 3x4-x2-3 equals 0?

x6 + 3x4 - x2 - 3 = 0 (x6 + 3x4) - (x2 + 3) = 0 x4(x2 + 3) - (x2 + 3) = 0 (x2 + 3)(x4 - 1) = 0 (x2 + 3)[(x2)2 - 12] = 0 (x2 + 3)(x2 + 1)(x2 - 1) = 0 (x2 + 3)(x2 + 1)(x + 1)(x - 1) = 0 x2 + 3 = 0 or x2 + 1 = 0 or x +… Read More

### How do you slove this problem 3x-111 x2 x?

There are some operators missing that make this rather ambiguous. If you mean: 3x - 111 + x2 = x and wish to solve for x, then here's the answer: x2 + 2x - 111 = 0 x2 + 2x + 1 = 112 (x + 1)2 = 112 x + 1 = ± √112 x = -1 ± 4√7 If you mean: 3x - 111 = x2 + x Then solving for x gives… Read More

### What is 3x2 divided by x2?

I am assuming that in this question x2 refers to x2 since otherwise the second term "x2" makes no sense. Then 3x2/x2 = 3.

### What is x2 plus 49?

x2 + 49 = x2 - (-49) = x2 - (-1)(49) = x2 - (i2)(72) = x2 - (7i)2 = (x - 7i)(x + 7i) where i is the imaginary square root of -1.

### X2 plus y - 52 equals 30?

x2 + y - 52 = 30 x2 - x2 + y - 52 + 52 = - x2 + 30 + 52 y = -x2 + 82 Since a = -1, the parabola open downward, and crosses the x-axis at x = +&- sq.root of 82. 0 = -x2 + 82 0 - 82 = -x2 + 82 - 82 -82 = -x2 82 = x2 +&- sq.root of 82 = x

### What is the pattern for the frogs in your sims agents?

yellow x2 green turquoise x2 green yellow orange red x2 orange yellow x2 orange x2

### What are the fruits in Pacman?

There is cherry,strawberry, orange x2, apple x2, lime x2, flag x2, gold bar x2, and then the rest is keys up to level 256.

### What is the factor of X4 plus X2 - 42?

x4 + x2 - 42 Let x2 = t, so that x4 = t2 t2 + t - 42 since -42 = 7(-6) and 7 + (-6) = 1, then t2 + t - 42 = (t - 6)(t + 7) = (x2 - 6)(x2 + 7) By replacing t with x2. So we have, x4 + x2 - 42 = (x2 - 6)(x2 + 7) = [x2 - (square root of 6)2](x2 + 7)… Read More

### If fx equals cossinx2 then f prime equals?

f(x)=cos(sin(x2)) [u(v)]' = u'(v) * v' so f'(x) = cos'(sinx(x2)) * sin'(x2) * (x2)' f'(x) = -sin(sin(x2)) * cos(x2) * 2x = -2x sin(sin(x2)) cos(x2)

### What is the answer of Athena's sisters riddle on mythology island?

the answer for Aphrodite puzzle are in this order Ares Hermes Aphrodite Artemis and hestia do them that order excaly no joke and a plus bonus i am going to tell you what medals I have early poptropica x2 shark tooth x2 time tangled x2 24 carrot x2 super power x2 spy x2 nabooti x2 counterfeit x1 big nate x2 astro knights x2 reality TV x2 mythology x1 skullduggery x1 steamworks x1 great pumpkin x2… Read More

### Sum of series 1 plus x2 plus x4.....plus xn?

(xn+2-1)/(x2-1) Explanation Let Y=1+x2+x4+...+xn. Now notice that: Y=1+x2+x4+...+xn=x2(1+x2+x4+...+xn-2)+1 Y+xn+2=x2(1+x2+x4+...+xn-2+xn)+1 Y+xn+2=x2*Y+1 Y+xn+2-x2*Y=1 Y-x2*Y=1-xn+2 Y(1-x2)=1-xn+2 Y=(1-xn+2)/(1-x2)=(xn+2-1)/(x2-1)

### What is the anti derivative of x divided by x squared minus 1?

The antiderivative of x/(x2-1) is ln(x2-1)/2. Proof: (ln(x2-1)/2)' = (1/(x2-1))*(x2-1)'/2=1/(x2-1)*(2x/2)=x/(x2-1).

### Solve the equation 11-x2 equals -5?

11-x2=-5 add -11 to both sides: 11-x2-11=-5-11 -x2=-16 divide both sides by -2: (-x2)/(-2)=(-16)/(-2) x=8 If the "x2" was supposed to be "x2", meaning exponentiation, ("x squared") and not "x2", implying multiplication, ("x times two") then we'd get: x2=16 x=±4

### What is the quadratic equation of -x2-4 equals 14 using the complex number system?

The equation is -x2 - 4 = 14 or -x2 = 18 which is the same as x2 = -18. That is the quadratic equation.

### What does Lego Indiana Jones score x2 do?

Simple, It dobules you money in game Eg: 10=20 100=200 1000=20000 10,000=20,000ect

### What is the derivative of 3cosx2?

I'm assuming your question reads "What is the derivative of 3cos(x2)?" You must use the Chain Rule. The derivative of cos(x2) equals -sin(x2) times the derivative of the inside (x2), which is 2x. So... d/dx[3cos(x2)] = -6xsin(x2)

### Determine what should replace the question mark and why A B D H P 32?

64. because every letter is replaced with the number of the position in the alphaeth, and then doubled. A=1 x2= B=2 x2= D=4 x2= H=8 x2= P=16 x2= 16 x2= 32 x2= 64

### What is a grouping factor for polynomial x3 ax 3a 3x2?

x3 + ax + 3a + 3x2 = x (x2 + a) + 3 (a + x2) = x (x2 + a) + 3 (x2 + a) = (x2 + a)(x + 3) Checking the work: x3 + ax + 3x2 + 3a or x3 + 3x2 + 3a + ax = x2 (x + 3) + a (3 + x) = x2 (x + 3) + a (x + 3) = (x + 3)(x2… Read More

### How do you differentiate the square root of 9-x2?

y = √(9 - x2) y = (9 - x2)1/2 y' = (1/2)(9 - x2)' y' = (1/2)(-2x) y' = -x

### When using the slope formula does it have to be (y2-y1)(x2-x1) or can it be (y1-y2)(x1-x2)?

If you mean: (y2-y1)/(x2-x1) and (y1-y2)/(x1-x2) then either works out the same.

### What is in a flaming dark light deck?

This deck contains. Monsters Flamvell firedog x2 flamvell magician x3 Flamvell guard x2 masked dragon x3 dread dragon x2 majestic dragon x2 worm caratos x2 worm dimikles x2 worm gulse x1 mystic tomato x3 changer synchron x2 reptilianne naga x2 drill barnicle x1 spells pot of avarice x1 pot of benevolence x2 monster reborn x1 cards of consonence x1 scapegoat x1 stardust shimmer x2 dark hole x1 heavy storm x1 burden of the mighty x1… Read More

### How do you factor 16-x2?

16 - x2 would be factored into (4-x) and (4+x) To double-check, multiply the factors: (4-x)(4+x) = 16 + 4x - 4x -x2 = 16 - x2